The Private Sector in Development : Entrepreneurship, Regulation, and Competitive Disciplines - Klein, Michael U. (Washington, DC: World Bank, 2013)
Over the years, the term private sector development, has been misunderstood and misconstrued - variously vilified and sanctified. During the decade of the 1990s, the role of the private sector in economic development, received increased attention, with controversy surrounding such issues as privatization, and corporate scandals. This book provides the first comprehensive treatment of the topic. Central to the discussion, is the design of public policy that promotes an appropriate balance between competition, and regulation. It places special emphasis on the means by which private initiative is channeled into socially useful directions, particularly job creation, and basic service delivery for poor people. Finally, there is discussion of the implications of private sector involvement for policies of development institutions. Written principally for policymakers, and advisers, the book thoroughly explores the challenges inherent in creating public policy that encourages, and enhances the development role of the private sector. If global poverty is to be reduced, the private sector, by almost unanimous assent, is crucial. The authors offer a broad-ranging, and balanced assessment of how to build workable, market mechanisms in developing countries.